Political Understanding. Issue 2 (23rd April 2023) - Lepoutre, Maxime
Abstract: Public opinion research has shown that voters accept many falsehoods about politics. This observation is widely considered troubling for democracy – and especially participatory ideals of democracy. I argue that this influential narrative is nevertheless flawed because it misunderstands the nature of political understanding. Drawing on philosophical examinations of scientific modelling, I demonstrate that accepting falsehoods within one's model of political reality is compatible with – and indeed can positively enhance – one's understanding of that reality. Thus, the observation that voters accept many political falsehoods does not necessarily establish that they lack political understanding. I then address three worries: that voters cannot generally engage in such political modelling; that political modelling obscures facts that are crucial to political understanding; and that successful political modelling would require knowing that one's model contains falsehoods. My responses reveal how, going forward, we should measure political ignorance, and they highlight the standing importance of participatory democracy.